تجزئة السوق المصرفي وأثرها على الميزة التنافسية - عائشة عبدالله مرزوق خليفة (Surman Journal of Science and Technology, 2025)
This study aims to demonstrate the impact of banking market segmentation on improving and developing all types of banking services. The descriptive-analytical approach was used, which relies on collecting data and information related to the study variables. The study sample consisted of 30 employees at Sahara Bank (Surman branch). To analyze and interpret the results of this study, SPSS was used with a package of statistical tests. The results of this study showed a relationship between banking market targeting strategies and the development and improvement of banking services provided. It was found that the bank's management adopts marketing strategies that enhance customer loyalty to the service and prevent competitors from influencing this loyalty.